INTERPRETATION OF THE 3D GEOELECTRICAL MODEL OF THE STEPPE CRIMEA BOWELS. EUPATORIA AND SAKI PROFILES - Burakhovich Т.; Kushnir А.; Ilienko, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The interpretation of the segment of the deep three-dimensional Crimean region geoelectrical model within the Saki and Yevpatoria profiles, built on the basis of the Earth’s low-frequency electromagnetic field experimental observations, was obtained in 2012 by the INSTITUTE OF GEOPHYSICS named after S.I.Subbotin. The main result of the analysis is the identification of vertical and horizontal alternation of high and low resistivity, both in the earth’s crust and in the upper mantle. It is shown that the geoelectrical sections along all the profile sections of the model are characterized by a dip to the north of the consolidated basement surface depth and, accordingly, an increase of the near-surface layer conductivity. The conductivity anomaly in the consolidated earth’s crust was revealed in the depth interval of 5-10 km with resistivity (ρ) of 5 Ohmꞏm, galvanically connected with the sedimentary cover. Deeper than 10 km, homogeneous and inhomogeneous layers in ρ alternate: 10-60 km with ρ = 1000 Ohmꞏm; 60-90 km with ρ = 100 and 1000 Ohmꞏm; 90-110 km with ρ = 1000 Ohmꞏm; 110-140 km with ρ = 40 and 1000 Ohmꞏm, the contact corresponds to the different ρ of normal geoelectrical sections of different-aged structures of the Scythian plate and the East European platform; also horizontally layered normal section. It has been analyzed that earthquake sources of the Steppe Crimea seismic region are concentrated in geoelectrically inhomogeneous zones and tend to contact structures with ρ differ - above the upper margin, outside and between the conductivity anomalies in the consolidated rocks of the earth’s crust. The considered material confidently indicates the confinement of hydrocarbon manifestations to the high electrical conductivity anomalies identified according to the data of geoelectromagnetical sounding and three-dimensional modeling, which are characterized by subvertical channels galvanically connected with sedimentary deposits, and layering in the earth’s crust and upper mantle. Geoelectrical inhomogeneities, which reflect the current state of the earth’s crust and upper mantle and are probably due to the influence of modern mantle fluids, correspond to manifestations of seismicity and hydrocarbon content.